1993
DOI: 10.1055/s-0038-1649606
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Recombinant Coagulation Factor 125I-rFVIIa in Rats

Abstract: SummaryRecombinant human factor VIIa (rFVIIa; NovoSeven®) is a two-chain activated clotting factor that is used in the treatment of haemophilia. The distribution of radioactivity in male and pregnant and non-pregnant female rats has been examined by whole-body autoradiography (WBA) after single intravenous doses of 125I-radiolabelled rFVIIa at a dosage level of ca. 0.1 mg/kg.Concentrations of radioactivity were highest in the blood and the highly perfused major thoracic and visceral organs and gonads. This dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…In addition to a high uptake of 18 F-FVIIai in the tumors, we noted an accumulation in the joint regions as previously described for 125 I-FVIIa in biodistribution studies in a rat model (32). Most likely this was due to a nonspecific interaction.…”
Section: Discussionsupporting
confidence: 83%
“…In addition to a high uptake of 18 F-FVIIai in the tumors, we noted an accumulation in the joint regions as previously described for 125 I-FVIIa in biodistribution studies in a rat model (32). Most likely this was due to a nonspecific interaction.…”
Section: Discussionsupporting
confidence: 83%
“…We demonstrated that the differences in clearance observed between rFVIIa:C and rFVII:Ag are explained by rFVIIa-AT complex formation. Prior studies suggest the liver is a major clearance organ for rFVIIa [10,11,21]. However, whether rFVIIa is cleared by the liver directly or in a complex is not known.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies in animals have addressed the in vivo clearance mechanism of rFVIIa. For example, in rats, distribution studies suggest that rFVIIa is widely distributed in the body, with the highest rFVIIa concentrations observed in highly perfused organs, such as the liver [10]. Also in rats, histopathological examinations of the liver suggest that rFVIIa is cleared by hepatocytes and kuppfer cells via clathrin-mediated endocytosis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, placental transfer of maternal FVII may account for the observed coagulopathy. However, a direct examination of maternal FVII levels in embryos failed to reveal such transfer, except when supraphysiological levels of maternal FVII were present (11,20). Additionally, the rescue of the intrauterine lethality associated with a TFPI deficiency by the additional loss of FVII suggests that any possible level of maternal FVII is insufficient to cause coagulopathy in these embryos (14).…”
mentioning
confidence: 99%